The traditional garments of Cuentepec native women: notes on the kueuitl (ModaPalavra e-periódico, 2025)
A Mexican indigenous community called Cuentepec preserves the traditional women's clothing known as kueuitl. The aim of this study was to explore the relationship between Nahua women from Cuentepec and their autochthonous dress. This ethnographic study primarily relied on participant observation, supplemented by interviews and bibliographic reviews. The photographs, reflections, and testimonies presented are the result of the researcher’s immersion in the community from May 2022 to January 2023. The research identified key elements of the traditional attire, concluding that it plays a fundamental role in the social dynamics of Cuentepec's women.
Keywords: indigenous garments; indigenous culture; traditional garments; autochthonous dress; Cuentepec; mexican garments; Nahua garments